Socio‐economic Status, Demographic Characteristics and Intimate Partner Violence. (17th July 2019) - Wilson, Nicholas
Abstract: One in three ever‐partnered women worldwide has experienced intimate partner violence (IPV), yet there is little systematic global evidence on the association between socio‐economic status (SES), demographic characteristics and IPV. This paper uses information from more than one‐quarter of one million female respondents age 15–49 in IPV modules from 36 Demographic and Health Surveys to provide detailed evidence on IPV gradients around the developing world. The analysis reveals relatively large negative IPV–SES gradients for respondent years of schooling and household wealth. Marriage and higher age are generally associated with lower IPV, whereas the physical violence–age profile follows an inverted U‐shape. © 2019 John Wiley & Sons, Ltd.